The Principle of Justice in the Legal Position of Suretyship in Indonesian Insolvency Law - Irfan, Faris Muhammad; Widhiyanti, Hanif Nur; Dewi, Amelia Sri Kusuma (International Journal of Business, Law, and Education, 2025)
This paper analyzes the legal position of suretyship (borg) in Indonesian bankruptcy and debt suspension (PKPU) proceedings, focusing on the principle of justice. The study addresses the incomplete norms in Law Number 37 of 2004, which do not explicitly regulate petitions against sureties. Using a normative juridical method based on statutory, conceptual, and case approaches, the research finds that sureties are often treated as debtors, even though the Indonesian Civil Code defines suretyship as accessory and subsidiary. Several court verdicts have accepted joint petitions against debtors and sureties without independent proof or separate legal assessment. This precedent undermines commutative and procedural justice, as the surety does not bear primary responsibility and is not a joint and several debtors. These findings indicate the need for legal reform to ensure that the surety receives separate procedural treatment aligned with their legal capacity.